Modelling and analyzing the surface fire behaviour in Hyrcanian forest of Iran - H. Aghajani; A. Fallah; S. Fazlollah Emadian (Journal of Forest Science, 2014)
The purpose of this study was to assess the forest fire behaviour and investigate the impact of different parameters on the spread of surface fire in the Hyrcanian forest of Iran. Surface fire was simulated using mathematical models in Microsoft Visual Basic 6.0 environment during a 30-minute time period. Several parameters that contributed to the speed of surface fire such as slope, wind velocity and litter thickness in the forest floor and various types of forest litter associated with hornbeam (Carpinus betulus L.), Persian ironwood (Parrotia persica C.A.M), beech (Fagus orientalis L.) and maple (Acer velutinum L.) were investigated. The results indicated that the maximum burned area was associated with beech litter. Forest surface fire demonstrated similar behaviour for the litter types of beech and Ironwood, whereas in the case of maple and hornbeam litters, the fire spread parallelly and perpendicularly to contour lines, respectively. The burned area increased in an irregular pattern as the forest floor slope gradient was increased. Moreover, the skewed pattern of the burned area for the forest floor composed of maple, beech, ironwood andhornbeam litter was described as high, low, moderate and low, respectively. The fire spread angle in forest floor associated with maple and beech litters changed with litter thickness. Finally, litter thickness had a significant effect on the direction of fire spread and this was more prominent with hornbeam litter.